CRIMINAL JUSTICE RESPONSES TO DOMESTIC ABUSE IN NORTHERN IRELAND - McQuigg, Ronagh J. A. ([S.l.] : ROUTLEDGE, 2022)
This book provides a detailed exploration of the responses of the criminal justice system to domestic abuse in Northern Ireland. The book's primary focus is on developments which have taken place since around 2010, and in particular since the restoration of the Northern Ireland Assembly in January 2020 after a three year suspension. The book includes discussion of the increased levels of domestic abuse in Northern Ireland in the context of the COVID-19 pandemic, and analyses the ways in which the criminal justice system responded. In addition, the book includes in-depth discussion of the Domestic Abuse and Civil Proceedings Act (Northern Ireland) 2021, which had the effect of criminalising coercive control, and the implications of this legislation for Northern Ireland's response to domestic abuse. The book will be of great interest to academics and researchers from a wide variety of disciplines, such as criminal law, criminology, social policy, human rights, family law, gender studies and sociology; as well as practitioners and those in the voluntary sector who are working in the area of combating domestic abuse. It can also be used on courses at both undergraduate and postgraduate levels which incorporate the topic of domestic abuse.
OCLC-licensed vendor bibliographic record.
Keywords: SOCIAL SCIENCE / Violence in Society; LAW / Criminal Law / General; SOCIAL SCIENCE / Women's Studies; Domestic relations -- Northern Ireland -- Criminal provisions